Transformation of the Linguistic Reasoning Paradigm of Basic Colour Terms: outline of the problem - Změlík, Richard (Bohemica Olomucensia, 2018)
The paper is focused on selected linguistic issues, which touch the problems of basic colour terms. Specially we concentrate on two domain of research. First of the research position understand the basic colour terms as so called linguistic universalities. The main argument of this point of view was given by another research of basic colour terms, which compare them with human ability to perception different wavelength of light. Second research position argue with cognitive processes of perception and explain the basic semantic of colour terms as result of so called language conceptualization of natural world. The goal of this paper is present the main change in linguistic paradigm, which concern research of basic colour terms and their semantics.
Keywords: basic colour terms; evolutionary model of basic colour terms; cognitive linguistics; language image of the world; semantics of basic colour terms